Kinetics of Combustion of Densified Fuels from Residues of Isabella Grape Processing (Vitis labrusca L.) (2018)
This paper presents the results of the kinetics of combustion by thermogravimetry of briquettes prepared with residues of vine shoots, skins, stalks and seeds, obtained from the cultivation and processing of Isabella grapes (Vitis labrusca L.). The briquettes were prepared by compression and characterized by near analysis, elemental analysis and thermogravimetric analysis (TGA). The TGA was carried out at three heating rates and in air atmosphere. With the results of the TGA the activation energy was determined by the Iso-conversion methods of Starink and Friedman, and the order of reaction by the Avrami method. The Starink method was found to be more accurate than the Friedman method in calculating activation energy. In addition, reaction order values are very similar for the residues and mixtures analyzed.